2006
DOI: 10.1590/s0100-29452006000200023
|View full text |Cite
|
Sign up to set email alerts
|

The ideal table grapes for the Spanish market

Abstract: This paper seeks to explore a survey of consumers in Spain. The survey explores the attributes of quality that consumers are seeking and promotion of grapes via "quality" marks, which are indicators of possible ways to increase demand. The reason consumers are switching to other foods, such as dairy based snacks, is that grapes are not easy to eat, can be unreliable in terms of their quality attributes, and their price more variable. Consumers are also generally unaware of the marks quality currently used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 2 publications
1
7
0
3
Order By: Relevance
“…However, safety cannot be searched or experienced unless provided by a third party to the consumer. Piva et al (2006) also reported that demand for grapes in Spanish markets can be improved by using quality marks. Further, consumers are willing to pay for sweetness than the size of the fruit.…”
Section: Results Of Rank Ordered Logistic Regressionmentioning
confidence: 99%
“…However, safety cannot be searched or experienced unless provided by a third party to the consumer. Piva et al (2006) also reported that demand for grapes in Spanish markets can be improved by using quality marks. Further, consumers are willing to pay for sweetness than the size of the fruit.…”
Section: Results Of Rank Ordered Logistic Regressionmentioning
confidence: 99%
“…Visual attributes such as colour, size and shape of the berry are primary characteristics that consumers observe . In addition to visual characteristics, physicochemical properties are involved in sensory and quality evaluation . Sensory descriptors such as skin friability, skin thickness and flesh firmness have been proposed to characterize commercial table grape cultivars…”
Section: Introductionmentioning
confidence: 99%
“…En Chile es escasa la información respecto a las preferencias de los consumidores y disposición a pagar por productos agrícolas orgánicos, y menos frutícolas, a pesar de los estudios que existen en países más desarrollados (NADEZHDA;MAZZOCCO, 2008;BOCCALETT;NARDELLA, 2000;BAKER, 1999). Específicamente, trabajos que identifiquen las preferencias de los consumidores por distintas características de uva de mesa son aún más escasos (PIVA et al, 2006), aunque en la literatura se encuentran artículos que relacionan a uvas orgánicas en la producción y preferencias por vino (CERDA, 2010;SANCHEZ;GIL, 1998). La falta de estudios relacionados también se refleja en la casi inexistencia de trabajos que busquen determinar la disposición a pagar (DAP) por la uva de mesa orgánica.…”
Section: Introductionunclassified